2014
DOI: 10.1016/j.jaac.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of DSM-IV Pervasive Developmental Disorder and DSM-5 Autism Spectrum Disorder Prevalence in an Epidemiologic Sample

Abstract: Objective Changes in autism diagnostic criteria found in DSM5 may affect Autism Spectrum Disorder (ASD) prevalence, research findings, diagnostic processes and eligibility for clinical and other services. Utilizing our published, total-population Korean prevalence data, we compute DSM5 ASD and Social Communication Disorder (SCD) prevalence and compare them to DSMIV Pervasive Developmental Disorder (PDD) prevalence estimates. We also describe individuals previously diagnosed with DSMIV PDD when diagnoses change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 10 publications
6
85
1
7
Order By: Relevance
“…Within DSM-5, individuals who have impairments in social communication but who lack restricted, repetitive behaviors or interests may be diagnosed with Social Communication Disorder. Kim et al (2014) found that 32 % of children who meet DSM-IV-TR criteria for PDD-NOS may meet the criteria for Social Communication Disorder. However, given that Social Communication Disorder is newly recognized within DSM-5, it might not be recognized by insurers or schools, potentially limiting access to treatment for children with clinically significant impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Within DSM-5, individuals who have impairments in social communication but who lack restricted, repetitive behaviors or interests may be diagnosed with Social Communication Disorder. Kim et al (2014) found that 32 % of children who meet DSM-IV-TR criteria for PDD-NOS may meet the criteria for Social Communication Disorder. However, given that Social Communication Disorder is newly recognized within DSM-5, it might not be recognized by insurers or schools, potentially limiting access to treatment for children with clinically significant impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of autism, currently estimated at >1 % [3], underscores the need to discover the biological substrates of this unique but heterogeneous disorder, including neuroanatomical abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the proportion of students with SEN in relation to the total number of students enrolled in the schools, it is possible to conclude that there is underdiagnosis of SEN cases, and consequently under-reporting of these cases to the education department. Taking autism spectrum disorder as an example, where the estimated prevalence is between 0.6 and 1% 13,14 , in this study only 0.05% of students were classified with this diagnosis.…”
Section: Discussionmentioning
confidence: 93%